การวิเคราะห์แผ่นบางบนฐานยืดหยุ่น - หอวิจิตร, ดร.อินทรชัย (Engineering and Applied Science Research, 2013)
An analysis of infinitely large thin plate on elastic foundation subjected to a concentrated force is presented. Using Hankel transforms, the deflection function of the plate and the corresponding bending moments and show force are obtained.